2021
DOI: 10.3389/fpubh.2021.668642
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless Tobacco Point of Sale Advertising, Placement and Promotion: Associations With Store and Neighborhood Characteristics

Abstract: Introduction: Objectives of this study were to determine retail and neighborhood characteristics associated with smokeless tobacco (ST) product promotion, price promotion, and storefront advertising among retailers in Oklahoma.Methods: In this statewide point-of-sale study, we collected data from 1,354 ST retailers. Using store characteristics and census tract information, we estimated summary statistics and adjusted prevalence ratios during 2019–2020.Results: Of ST retailers audited, 11.0% demonstrated ST you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Only one cigarette ad had a cross-promotion to IQOS (via a QR code). Similarly, a study assessing smokeless tobacco POS advertisement found that only 0.3% offered cross-promotions with cigarettes 35. On the other hand, cross-promotion has been observed in other tobacco companies’ advertisements for nicotine pouches,36 and in direct mailings 37…”
Section: Discussionmentioning
confidence: 98%
“…Only one cigarette ad had a cross-promotion to IQOS (via a QR code). Similarly, a study assessing smokeless tobacco POS advertisement found that only 0.3% offered cross-promotions with cigarettes 35. On the other hand, cross-promotion has been observed in other tobacco companies’ advertisements for nicotine pouches,36 and in direct mailings 37…”
Section: Discussionmentioning
confidence: 98%
“…Our analysis also has implications for contractual arrangements implemented through retailers or wholesalers. Cigarettes and smokeless tobacco have been sold primarily through mainstream brick-and-mortar retail, especially convenience, drug and grocery stores, where tobacco companies provide slotting allowances to secure shelf space 39 80 81. Part of the promotional allowance expenditures is for branded shelving, complementing the small portion (0.8%) devoted to retail advertising.…”
Section: Discussionmentioning
confidence: 99%